Expression of connexins 40 and 43 in human left atrium in atrial fibrillation of different aetiologies. (18th January 2005) - Wetzel, U; Boldt, A; Lauschke, J; Weigl, J; Schirdewahn, P; Dorszewski, A; Doll, N; Hindricks, G; Dhein, S; Kottkamp, H
Abstract : Objective: To test the hypothesis that atrial fibrillation (AF) is associated with changes in the expression of connexins 40 and 43 in the left atrium with more pronounced changes in mitral valve disease than in lone AF. Methods: Protein concentrations of connexin 40 and connexin 43 were analysed in left atrial tissue of patients undergoing cardiac surgery. One group of patients had lone AF (n  =  41), one group had AF and mitral valve repair (n  =  36), and one group in sinus rhythm served as controls (n  =  15). Results: Western blot analysis of connexin 40 and connexin 43 expression showed an increase of both gap junctional proteins (connexin 43 > connexin 40) in patients with AF of all forms compared with patients in sinus rhythm (p  =  0.01 and p  =  0.011, respectively). Subgroup analysis showed increased concentrations of connexin 40 in lone AF and AF with mitral valve disease compared with sinus rhythm (p  =  0.06 and p  =  0.029, respectively), whereas the same analysis for connexin 43 reached significance only in the mitral valve disease group (p  =  0.031). No differences in connexin 40 and connexin 43 expression were detectable between lone AF and AF with mitral valve disease. Within the groups connexin 40 and connexin 43 expression did not differ between patients with paroxysmal AF and patients with chronic AF. Conclusion: The present study shows for the first time that AF can induce changes in the left atrium with increased connexin expression. Furthermore, no systematic differences between patients with paroxysmal and chronic AF were detected.